Robotics and Automation with Artificial Intelligence: Improving Efficiency and Quality - Hussain, Nazim; Pangilinan, Greian April (Aptisi Transactions On Technopreneurship (ATT), 2023)
The industrial and technological revolutions are accelerating globally as a result of the widespread adoption of new information and communication technologies like artificial intelligence (AI), the Internet of Things (IoT), and blockchain technology. Government, business, and academia are all paying close attention to artificial intelligence. In this study, a selection of well-read articles on artificial intelligence from recent publications is examined. The focus of this study is to offer an analysis of artificial intelligence using integrated industry information. It provides an overview of the extent of artificial intelligence using background information, motivating factors, technological advancements, and applications, as well as rational predictions for its future. This study can contribute to the field of artificial intelligence research and offer crucial knowledge to real-world practitioners. This study's key contribution is its clarification of the current state of the art in AI for further research.